1956
DOI: 10.1017/s0022112056000135
|View full text |Cite
|
Sign up to set email alerts
|

The law of the wake in the turbulent boundary layer

Abstract: SUMMARYAfter an extensive survey of mean-velocity profile measurements in various two-dimensional incompressible turbulent boundarylayer flows, it is proposed to represent the profile by a linear combination of two universal functions. One is the well-known law of the wall. The other, called the law of the wake, is characterized by the profile at a point of separation or reattachment. These functions are considered to be established empirically, by a study of the mean-velocity profile, without reference to any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
701
2
6

Year Published

1972
1972
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,426 publications
(738 citation statements)
references
References 12 publications
29
701
2
6
Order By: Relevance
“…(2), relatively consistent values have been found in different literature studies. A range of j = 0.40-0.42 was proposed for the flows over smooth bed investigated by Coles [6] and Cardoso et al [4]; while, similar value (j = 0.40) was also suggested for the rough bed flow by Song et al [30]. More recently, Auel et al [2] summarised from various smooth and rough bed flow studies that j = 0.385-0.435, universally.…”
Section: Uniform Flow Results and Analysismentioning
confidence: 63%
See 2 more Smart Citations
“…(2), relatively consistent values have been found in different literature studies. A range of j = 0.40-0.42 was proposed for the flows over smooth bed investigated by Coles [6] and Cardoso et al [4]; while, similar value (j = 0.40) was also suggested for the rough bed flow by Song et al [30]. More recently, Auel et al [2] summarised from various smooth and rough bed flow studies that j = 0.385-0.435, universally.…”
Section: Uniform Flow Results and Analysismentioning
confidence: 63%
“…More recently, Auel et al [2] summarised from various smooth and rough bed flow studies that j = 0.385-0.435, universally. For the log-law integration constant B r of smooth bed uniform flows, it was proposed as B r = 4.9 in Mellor and Gibson [15], and Anwar and Atkins [1]; and B r = 5.1 in Coles [6], and Cardoso et al [4]. In comparison to different rough bed flow studies (i.e.…”
Section: Uniform Flow Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…the law of the wall, and the velocity defect law. Both of these are contained within the composite boundary-layer profile used by Coles (1956): where V, = (~, / p ) $ is the friction velocity, Y is the kinematic viscosity, K is the von K&rm&n constant = 0.41,ii is the wake strength, W(y/6) is the wake function, and 6 is the local boundary-layer thickness. Further, although the data show considerable scatter, the wake strength parameter ii appears to be reasonably correlated with Clauser's (1 956) equilibrium pressure gradient parameter / 3 = (&*/T,) (dp/dx), indicating that most of the data represent a state of local equilibrium and are not strongly dependent on their upstream history.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors [Coles, 1956;Finley et al, 1966;Coleman, 1981;Zippe and Graf, 1983] suggested that the deviations of (1) from velocity measurements are not accounted by adjusting A and B but, rather, by adding a divergence function ok(z). Coles [1956] extended the applicability of (1), introducing a purely empirical divergence function [Nezu and Rodi, 1986]: cos: ( tb(z) = b2z2(1 -z) + b3z2(3 -2z),…”
mentioning
confidence: 99%